Fatty acid, triglyceride, and kinetic properties of milk fat fractions made by the combination of dry fractionation and short-path molecular distillation - Huiquan Zhu; Xin Si; Yunna Wang; Panpan Zhu; Xiaoyang Pang; Xiaodan Wang; Marie-Laure Fauconnier; Ning Ju; Shuwen Zhang; Jiaping Lv (Journal of Dairy Science, 2023)
ABSTRACT: In this study, we aimed to detect the physicochemical properties of distilled products (residue and distillate) obtained from anhydrous milk fat (AMF) and its dry fractionation products (liquid and solid fractions at 25°C [25 L and 25 S]). The results showed that the saturated fatty acids and low- and medium molecular–weight triglycerides were easily accumulated in the distillate, and the percentage of unsaturated fatty acid and high molecular–weight triglycerides in the residue were higher, and these components in 25 S and 25 L were influenced more significantly than those in the AMF. In addition, the distillate had larger melting ranges in comparison with the distilled substrate, while the melting ranges of residue was smaller. The triglycerides were presented as the mixture crystal forms (α, βʹ, and β crystal) in 25 S, AMF, and their distilling products, and it was transformed gradually to a single form as the increasing of distilling temperature. Moreover, the accumulated pattern of triglycerides was double chain length in 25 S, AMF, and their distilling products. These results provide a new approach to obtain the milk fat fractions with different properties, and the findings of this study enrich the theoretical basis of milk fat separation in practical production.